Pengaruh Bauran Pemasaran Bagi Peserta Sellers Terhadap Keputusan Berpartisipasi Dalam Kegiatan Bali & Beyond Travel Fair 2019 di ASITA Bali. - Ni Luh Putu Septiani Putri Darmayanti; Ketut Arjaya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
MICE tourist visits are expected to increase every year and can have a positive impact on 13 MICE tourist destinations, one of which is the island of Bali. The increase in MICE tourist visits in Bali is increasing because of the implementation of MICE activities every year, which is exhibition. One of the international exhibition activities held every year in Bali is the Bali & Beyond Travel Fair. This study aims to determine how the impact of the service marketing mix (7P) which consists of product, place, price, promotion, process, personnel, and physical evidence for sellers on the decision to participate in BBTF activities as a place for marketing products and services from companies (sellers). The number of samples used was 83 respondents who participated in the BBTF from 2018 – 2019. The results of the study indicate that there are 3 (three) variables that significantly impact the participation decision of the marketing mix, are product, price, and place. In contrast, the other 4 (four) variables, promotion, process, personnel, and physical evidence have no significant effect. However, jointly impact the participation decision on the marketing mix significantly by 43.7% and the remaining 56.30% is a participation decision influenced by other factors.